To eat or not to eat—an exploratory randomized controlled trial on fasting and plant-based diet in rheumatoid arthritis (NutriFast-Study) - Hartmann, Anika M.; Dell'Oro, Melanie; Spoo, Michaela; Fischer, Jan Moritz; Steckhan, Nico; Jeitler, Michael; Häupl, Thomas; Kandil, Farid I.; Michalsen, Andreas; Koppold-Liebscher, Daniela A.; Kessler, Christian S. (Frontiers in Nutrition, 2022)
Background. Fasting is beneficial in many diseases, including rheumatoid arthritis (RA). Objective. This exploratory RCT compares the effects of a 7-day fast followed by a plant-based diet (PBD) to the effects of dietary recommendations of the German society for nutrition (Deutsche Gesellschaft für Ernährung, DGE) on RA disease activity, cardiovascular (CV) risk factors, and wellbeing. Methods. In this RCT we randomly assigned 53 RA patients to either a 7-day fast followed by an 11-week PBD or a 12-week standard DGE diet. Primary endpoint was the group change from baseline to 12 weeks on the Health Assessment Questionnaire Disability Index (HAQ-DI). Further outcomes included other disease activity scores, body composition, and quality of life. Results. Of 53 RA patients enrolled, 50 participants (25 per group) completed the trial and were included into the per-protocol analysis. The primary endpoint was not statistically significant. However, HAQ-DI improved rapidly in the fasting group the by day 7 and remained stable over 12 weeks (∆-0.29, p=0.001), while the DGE group improved later at 6 and 12 weeks (∆-0.23, p=0.032). DAS28 ameliorated in both groups by week 12 (∆-0.97, p<0.001 and ∆-1.14, p<0.001; respectively), with 9 patients in the fasting but only 3 in the DGE group achieving ACR50 or higher. CV risk factors including weight improved stronger in the fasting group than in the DGE group (∆-3.9 kg, p<0.001 and ∆-0.7 kg, p=0.146). Conclusions. Compared with a guideline-based anti-inflammatory diet, fasting followed by a plant-based diet showed no benefit in terms of function and disability after 12 weeks. Both dietary approaches had a positive effect on RA disease activity and cardiovascular risk factors in patients with RA.